2012
DOI: 10.1515/jpm-2012-0015
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of gestational diabetes in advanced economies

Abstract: This review provides a comprehensive and sound summary of the current state of research on the prevalence of GDM in advances economies as a fi rst step in identifying starting points for future interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
81
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(88 citation statements)
references
References 27 publications
4
81
0
3
Order By: Relevance
“…Our finding of 8.3% GDM among Rwandan women is largely comparable with data from developed countries: 3.2-7.6% in the US and 2.0-11.6% in Europe, (Schneider et al 2012) as well as data from Africa: 4.5%-13.4% in Nigeria, (Anzaku & Musa 2013) 3.7% in Ethiopia (Seyoum et al 1999) and 3.8-8.8% in South Africa . (Mamabolo et al 2007).…”
Section: Discussionsupporting
confidence: 87%
“…Our finding of 8.3% GDM among Rwandan women is largely comparable with data from developed countries: 3.2-7.6% in the US and 2.0-11.6% in Europe, (Schneider et al 2012) as well as data from Africa: 4.5%-13.4% in Nigeria, (Anzaku & Musa 2013) 3.7% in Ethiopia (Seyoum et al 1999) and 3.8-8.8% in South Africa . (Mamabolo et al 2007).…”
Section: Discussionsupporting
confidence: 87%
“…Perhaps the most important of these was the observed increase in GDM prevalence, especially when applied universally. 5,6 This led other bodies to maintain the previous two-step diagnostic and screening procedures. 1 In 2013, the World Health Organization (WHO) recommended the IADPSG criteria, 1 although it warned of possible difficulties in implementing them.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of GDM varies between populations, ranging from 1.7% to 11.6% [1]. Numerous studies found that GDM is associated with significantly higher maternal (cesarean section, gestational hypertension, preeclampsia), perinatal (macrosomia and birth injury) and postnatal (early onset of metabolic syndrome, diabetes and hypertension in children) complications risk [2,3].…”
Section: Introductionmentioning
confidence: 99%